The link between mental health-related discrimination and suicidality: service user perspectives. Issue 10 (July 2015) - Farrelly, S.; Jeffery, D.; Rüsch, N.; Williams, P.; Thornicroft, G.; Clement, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Suicide is a major global public health issue. Mental illness is a risk factor for suicide, but as many individuals with a diagnosed mental health problem do not experience suicidal ideation or attempt suicide, other individual and societal factors must be considered. Mental illness-related discrimination is one potential risk factor. Method Using mixed methods, the influence of discrimination on suicidality amongst 194 individuals diagnosed with depression, bipolar or schizophrenia spectrum disorders was investigated. Qualitative interviews with a sub-sample of 58 individuals who reported a link between experience of discrimination and suicidality were analysed using framework analysis. Quantitative methods were used to examine the model derived from qualitative analyses. Results Results indicate that the experience of discrimination led 38% of the overall sample of 194 participants, to suicidal feelings and 20% reported that it contributed to making a suicide attempt. The qualitative model derived from interviews with a sub-sample of 58 participants suggested that the experience of discrimination is experienced as a stressor that exceeds coping resources, leading to a negative self-image and a perception of decreased supportive networks/social structure. The anticipation of further negative events and treatment, and the perception of a lack of supportive networks led individuals in this study to feelings of hopelessness and suicidality. Quantitative analyses provided support for the model. Conclusions These data suggest that both psychological therapies aimed at improving coping skills and population-level anti-stigma interventions that reduce the occurrence of discrimination may provide some protection against suicide amongst individuals with mental health problems.